Exploring Wells-Dawson Clusters Associated With the Small Ribosomal Subunit - Crans, Debbie C.; Sánchez-Lombardo, Irma; McLauchlan, Craig C. (Frontiers in Chemistry, 2019)
The polyoxometalate P2W18O626-, the Wells-Dawson cluster, stabilized the ribosome sufficiently for the crystallographers to solve the phase problem and improve the structural resolution. In the following we characterize the interaction of the Wells-Dawson cluster with the ribosome small subunit. There are 14 different P2W18O626- clusters interacting with the ribosome, and the types of interactions range from one simple residue interaction to complex association of multiple sites including backbone interactions with a Wells-Dawson cluster. Although well-documented that bridging oxygen atoms are the main basic sites on other polyoxometalate interaction with most proteins reported, the W=O groups are the main sites of the Wells-Dawson cluster interacting with the ribosome. Furthermore, the peptide chain backbone on the ribosome host constitutes the main sites that associate with the Wells-Dawson cluster. In this work we investigate the potential of one representative pair of closely-located Wells-Dawson clusters being a genuine Double Wells-Dawson cluster. We found that the Double Wells-Dawson structure on the ribosome is geometrically sound and in line with other Double Wells-Dawson clusters previously observed in the solid state and solution. This information suggests that the Double Wells-Dawson structure on the ribosome is real and contribute to characterization of this particular structure of the ribosome.